2011
DOI: 10.3892/etm.2011.365
|View full text |Cite
|
Sign up to set email alerts
|

TEM observation of ultrasound-induced mitophagy in nasopharyngeal carcinoma cells in the presence of curcumin

Abstract: Abstract. The present study was designed to observe the initiation of mitophagy in tumor cells after ultrasound treatment in the presence of curcumin under transmission electron microscopy. Nasopharyngeal carcinoma CNE2 cells were incubated with 10 µM curcumin and then exposed to ultrasound for 8 sec at an intensity of 0.46 W/cm 2 . Severely swollen mitochondria, disrupted mitochondria and mitophagy were noted in the CNE2 cells after ultrasound treatment in the presence of curcumin. Our findings demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Moreover, it has been demonstrated that curcumin activates mitophagy. This finding underlines the importance of mitophagy in the process of cell death of nasopharyngeal carcinoma cells [118]. …”
Section: Potentially Targetable Metabolic Actors By Natural Compoundsmentioning
confidence: 61%
“…Moreover, it has been demonstrated that curcumin activates mitophagy. This finding underlines the importance of mitophagy in the process of cell death of nasopharyngeal carcinoma cells [118]. …”
Section: Potentially Targetable Metabolic Actors By Natural Compoundsmentioning
confidence: 61%
“…Several curcumin-mediated pharmacological effects have been described, including antiinflammatory [36][37][38], immunomodulatory [39], antitumor and chemosensitizing [40][41][42], anti-ischemic [43], hepatoprotective [44], relaxant [45], and antiasthmatic effects [46,47]. Effects of curcumin (10 μM) on the viability of nasopharyngeal carcinoma CNE2 cells exposed to ultrasound were investigated by Wang et al In their study, ultrastructure of mitochondria was disrupted and mitophagy was induced by curcumin in CNE2 cells [48].…”
Section: Cancermentioning
confidence: 99%
“…The therapy's effectiveness has also been demonstrated in more deeply located tumors including those of the central nervous system (Ohmura et al 2011; Gao et al 2013; Jeong et al 2012). Post-therapy histologic studies have consistently shown damage to the ultrastructure of the cancer cells including destruction of cell membranes, mitochondrial swelling and chromatin condensation (Liu et al 2006[b], 2007[a, b], 2008; Wang et al 2008[a], 2011[c], 2012[b]); it was considered that these changes induced by the therapy may have mediated cancer cell death. Combining photodynamic therapy with sonodynamic therapy had a synergistic effect in solid tumors with additional post-therapy tumor necrosis, inhibition of tumor growth and increased survival times (Jin et al 2000; Tserkovsky et al 2012).…”
Section: Sonodynamic Therapymentioning
confidence: 99%